Catalyzing green total factor productivity through digital innovation: mechanisms, evidence, and policy implications from urban China - Yao, Lu; Lu, Cheng (Frontiers in Environmental Science, 2025)
IntroductionDigital technological innovation has emerged as a crucial catalyst in balancing economic growth with environmental sustainability. In the context of high-quality development, understanding how digital innovation contributes to green total factor productivity (GTFP) is of growing importance, particularly amid global efforts toward decarbonization and industrial transformation.MethodsThis study investigates the impact and underlying mechanisms of digital technological innovation on green total factor productivity (GTFP) by constructing a panel dataset comprising 278 Chinese prefecture-level cities from 2007 to 2022. To examine both the direct and indirect effects, the analysis applies a range of econometric methods, including fixed effects models, mediation models, and instrumental variable estimation. Robustness of the results is verified through alternative specifications, exclusion of outliers, lagged variables, and policy-based instruments.ResultsThe empirical findings demonstrate that digital technological innovation exerts a significant positive impact on GTFP, with each one-unit increase in the digital innovation index leading to an estimated 0.8% improvement in carbon emission efficiency. Further mediation analysis suggests that this enhancement in GTFP is primarily driven by two interrelated mechanisms: the intensification of green technological innovation activities and the advancement of industrial structure toward more sustainable configurations. Additionally, heterogeneity analysis reveals that the strength and direction of this relationship vary notably across cities, depending on their specific resource endowments, the strength of intellectual property protection, and the extent of engagement in green policy pilot initiatives.DiscussionThese findings underscore the importance of integrating digital and green development pathways. To fully harness the potential of digital innovation for promoting green productivity, policymakers should foster a collaborative digital-green innovation ecosystem, improve institutional support for green technology diffusion, and coordinate industrial policies that jointly advance digitalization and environmental goals. City-specific strategies should leverage local strengths to facilitate the emergence of new digital-green industries.